Detecting Early Biomechanical Effects of Zoledronic Acid on Femurs of Osteoporotic Female Rats - Evandro Pereira Palacio; Sérgio Swain Müller; Trajano Sardenberg; Roberto Ryuiti Mizobuchi; José Antônio Galbiatti; Alcides Durigan; Aniello Savarese; Érika Veruska Paiva Ortolan (Journal of Osteoporosis)
Aim. To investigate the biomechanical effects of zoledronic acid (ZA) on femurs of female osteoporotic rats after follow-up periods of 9 and 12 months. Methods. Eighty female Wistar rats were prospectively assessed. At 60 days of age, the animals were randomly divided into two groups: bilateral oophorectomy (O) (n=40) and sham surgery (S) (n=40). At 90 days of age, groups O and S were randomly subdivided into four groups, according to whether 0.1 mg/kg of ZA or distilled water (DW) was intraperitoneally administered: OZA (n=20), ODW (n=20), SZA (n=20), and SDW (n=20). The animals were sacrificed at 9 and 12 months after the administration of the substances, and then their right femurs were removed and analyzed biomechanically. Axial compression tests that focused on determining the maximum load (N), yield point (N), and stiffness coefficient (N/mm) of the proximal femur were performed in the biomechanical study. Results. ZA significantly increased the maximum load and yield point, reducing the stiffness coefficient concerning the oophorectomy status and follow-up period. Conclusion. Zoledronic acid, at a dose of 0.1 mg/kg, significantly increased the maximum loads and yield points and reduced the stiffness coefficients in the femurs of female rats with osteoporosis caused by bilateral oophorectomy.